Biaya Audit Ditinjau dari Efektivitas Komite Audit, Peluang Investasi, Kendala Finansial dan Komplekitas Perusahaan - Megawati Oktorina; Molan, Agustiana Yudith (APSSAI, 2022)
The purpose of this study to examine the effect of audit committee effectiveness, investment opportunities, financial constraints and company complexity on the audit fee. This study uses a sample of companies listed on the IDX in 2016 – 2020 which disclose audit fees. The method to analyze the data using multiple linear regression analysis. The results shows that the effectiveness of the audit committee decrease audit fee. The investment opportunities and the company complexity increase the audit fees. However, the results of the study do not prove any significant effect of financial constraints on the audit fee. Suggestions for further research are that the company complexity is measured by the number of subsidiaries, including other factors such as corporate governance, size of public accounting firm, sales volatility and industrial sector. Keywords: Audit Fee; Company Complexity; Financial Constraints; Investment Opportunities